Open Innovation : Corporate Incubator - Latouche, Pascal (London, UK : Wiley-ISTE ; Hoboken, NJ : John Wiley and Sons, Inc., 2019)
The corporate start-up incubator is currently developing in large companies as an essential approach to open innovation. It faces a global system involving varied contexts, issues and actors. Its implementation is an art and to succeed the corporate incubator must become a real "interaction architect". Using testimonials and real case studies, the author takes a dive into the structural and social mysteries of corporate incubators. By analyzing the complex mechanisms of interactions, this book decrypts and reveals the keys to the success of these devices and to opening innovation in a broad sense. The concept of an "interaction architect" is related to the art of building fruitful interactions within human systems. Being aware that social systems exist is good, but knowing how to manage them is better
Chapter 1. Innovation: a story without an end -- Chapter 2. Incubators and other accelerators: the joys of diversity? -- Chapter 3. The architects of interactions: the four strategic access points -- Chapter 4. Topography: the characteristics of a structure -- Chapter 5. Adaptation in situ: levers for manipulation -- Chapter 6. When practice becomes the model to follow: the adoption of CI -- Chapter 7. CI example A: the "boss's thing" -- Chapter 8. CI example B: money doesn't make you happy -- Chapter 9. CI example C: reducing the wide gap -- Chapter 10. CI example D: "two-pillar" centralism -- Chapter 11. CI example E: the art of pivot.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 22, 2019).
John Wiley and Sons
Keywords: New business enterprises -- Management; Business networks -- Management; Business enterprises -- Technological innovations; Nouvelles entreprises -- Gestion; x; Entreprises -- Innovations; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business enterprises -- Technological innovations; Business networks -- Management; New business enterprises -- Management